(untitled) (Revista Contexto & Saúde, 2023)
Introduction: Breast cancer (BC) is the malignant neoplasm with highest incidence and mortality among women worldwide. Nutritional status (NS) before and after chemotherapy treatment can be decisive for prognosis and survival of the patient with BC. Objective: Systematic review of the NS before and after chemotherapy in women with BC. Methods: An extensive search on Pubmed, Web of Science, and Scopus databases was conducted. It was limited to manuscripts published until 2020 using the Boolean method with the following combinations of descriptors: “breast cancer” AND “nutritional status” AND “chemotherapy”. Results: A total of 12 articles were included in this review. Two studies with patients diagnosed with eutrophic and 10 studies with overweight patients addressed pre-chemotherapy NS. For post-treatment NS, nine studies enrolled overweight patients, two with eutrophic patients and one with patients at nutritional risk. Conclusion: Several studies confirm the association of BC and overweight/obesity with increased prevalence of the disease, poor prognosis, and reduced survival after the end of the treatment. Current data support the need for interventions in the patients’ lifestyle. Further studies on the association between interventions in BC should be conducted in order to form a larger body of evidence.